2014
DOI: 10.1111/ijsa.12078
|View full text |Cite
|
Sign up to set email alerts
|

Moving Forward Indirectly: Reanalyzing the validity of employment interviews with indirect range restriction methodology

Abstract: This study provides updated estimates of the criterion-related validity of employment interviews, incorporating indirect range restriction methodology. Using a final dataset of 92 coefficients (N = 7,389), we found corrected estimates by structural level of .20 (Level 1), .46 (Level 2), .71 (Level 3), and .70 (Level 4). The latter values are noticeably higher than in previous interview meta-analyses where the assumption was made that all restriction was direct. These results highlight the importance of conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 70 publications
1
59
2
1
Order By: Relevance
“…This difference is likely due to the increased number of highly structured interviews in their sample. Forty-six of the 73 studies (63%) in the Huffcutt et al (2014) sample were at the highest level of structure, whereas only 27 of 64 studies (42%) in the current study were highly structured.…”
Section: Resultscontrasting
confidence: 49%
See 3 more Smart Citations
“…This difference is likely due to the increased number of highly structured interviews in their sample. Forty-six of the 73 studies (63%) in the Huffcutt et al (2014) sample were at the highest level of structure, whereas only 27 of 64 studies (42%) in the current study were highly structured.…”
Section: Resultscontrasting
confidence: 49%
“…Using inter-rater reliability estimates from Table 1, corrections were made at the different levels of structure (low = .50, medium = .61, and high = .84). A range restriction ratio of .74 was used following Huffcutt et al (2014). Finally, the value of .52 was used to correct for unreliability in the criterion (Huffcutt et al, 2014;Rothstein, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of how structured interviews fare in practice, researchers have consistently found that highly structured interviews, compared to their unstructured counterparts, are preferable as they tend to be more reliable (Conway, Jako, and Goodman 1995;Huffcutt, Culbertson, and Weyhrauch 2013), better predictors of job performance (Huffcutt, Culbertson, and Weyhrauch 2014;Wiesner and Cronshaw 1988), and fairer, with fewer mean differences on the basis of sex and race (Huffcutt and Roth 1998).…”
Section: The Influence Of Interview Standardization On Communicationmentioning
confidence: 99%